Length and Weight Relationship of Mackerel Fish (Auxis rochei) at Fish Collector Markets in Ampenan, Lombok - Ulya Nisa Afifa; Dining Aidil Candri; AA Ngurah Nara Kusuma; Hilman Ahyadi; Yuliadi Zamroni (Jurnal Biologi Tropis, 2023)
Lisong tuna (Auxis rochei) is one of high economic potential value of fish because of its abundance and often found in the fish market in Ampenan. Evaluating the impact of fishing to the growth pattern of length-weight of tuna is needed to ensure the sustainability of lisong tuna population. It is feared that the high intensity of tuna (A. rochei) fishing can cause growth disturbances and a decrease in local tuna populations. This study aimed to determine the relationship between the weight and length of lisong tuna (A. rochei) to their growth patterns in the fish market of Ampenan. Thirty individuals of lisong tuna were collected from two fish markets, Bintaro and Kebon Roek, in Ampenan. The equation of Linear Allometric Model is used to evaluate the length and weight relationship in growth patterns of lisong tuna. This study resulted in the positive allometric growth pattern of lisong tuna with slope value more than 3 (b=3.79). It indicated that the lisong tuna which were collected in Bintaro and Kebon Roek markets have a weight growth rate faster than their length growth rate. It means that the lisong tuna sold in Ampenan markets is quite fleshy and has a good growth rate.